Utilization of Lightning Energy As a Lightning Power Plant to Optimize Lightning Potential in Medan City - Rizky Agassy Sihombing; Jennie Febrina Hutagalung; Jenita Br. Tambunan (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2022)
In addition to solar, wind, and water waves, there are other sources of energy that are renewable. Researchers are currently testing the use of these energies with a device that can draw electricity from the air. The new energy is electricity in the air that triggers the formation of lightning & lightning. The need for electrical energy is increasing day by day. Electrical energy supply in Indonesia itself is usually supplied from power plants such as Hydroelectric Power (PLTA), Air (PLTU), Solar (PLTS), Diesel (PLTD), and Geothermal (PLTG) whose existence still does not meet electricity needs. The type of research used is descriptive qualitative research by literature study use 10 journals. The purpose of this work is to utilize lightning as an energy source in order to maximize the potential of Indonesia's natural resources, especially in the city of Medan. The results show that lightning can be used as an alternative energy source, because lightning is a renewable energy and will not run out even if it is used continuously.